2009
DOI: 10.1021/ja905015x
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted Ammonia Borane Hydrogen-Release

Abstract: The strong non-nucleophilic base bis(dimethylamino)naphthalene (Proton Sponge, PS) has been found to promote the rate and extent of H(2)-release from ammonia borane (AB) either in the solid state or in ionic-liquid and tetraglyme solutions. For example, AB reactions in 1-butyl-3-methylimidazolium chloride (bmimCl) containing 5.3 mol % PS released 2 equiv of H(2) in 171 min at 85 degrees C and only 9 min at 110 degrees C, whereas comparable reactions without PS required 316 min at 85 degrees C and 20 min at 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 48 publications
4
114
0
3
Order By: Relevance
“…However, both require that the substrate, ammonia borane in this case, be in a liquid state. A number of approaches to developing liquid storage materials were examined ranging from solutions of ammonia borane in water and in conventional organic solvents to more concentrated solutions of ammonia borane in IL (low melting organic salts) as demonstrated by Sneddon and his colleagues, [88][89][90][91][92] to various organic amine derivatives of ammonia borane that had melting points at or below room temperature in a few cases. The CHSCoE's research began by exploring the homogeneous catalyst approach owing to its experimental simplicity, and with the hope that this could guide future heterogeneous catalyst selection.…”
Section: Catalytic Release Of Hydrogen From Ammonia Boranementioning
confidence: 99%
“…However, both require that the substrate, ammonia borane in this case, be in a liquid state. A number of approaches to developing liquid storage materials were examined ranging from solutions of ammonia borane in water and in conventional organic solvents to more concentrated solutions of ammonia borane in IL (low melting organic salts) as demonstrated by Sneddon and his colleagues, [88][89][90][91][92] to various organic amine derivatives of ammonia borane that had melting points at or below room temperature in a few cases. The CHSCoE's research began by exploring the homogeneous catalyst approach owing to its experimental simplicity, and with the hope that this could guide future heterogeneous catalyst selection.…”
Section: Catalytic Release Of Hydrogen From Ammonia Boranementioning
confidence: 99%
“…For example, the H 3 BNH 2 -Li + salt has previously been prepared in situ from AB and n-BuLi at 0 o C. 56 More recently, ball milling 55,58,59 and solution reactions 60,61 of AB with metal hydrides have been used to generate H 3 BNH 2 -M + (M = Li and Na) and (H 3 BNH 2 -) 2 Ca 2+ . We found 29 that AB deprotonation could also be easily achieved by its reaction with either lithium or potassium triethylborohydride (Equation 4.7), but that in these cases, a Et 3 B-stabilized anion was formed, with the observed resonances in the 11 B NMR spectra of the Li + (-7.5 (s) and -23.8 (q) ppm) and K + (-7.8 (s) and -23.6 (q) ppm) compounds being assigned based on the DFT/GIAO calculations to the BEt 3 -(calc -10.6) and terminal -BH 3 The structures of H 3 BNH 2 -M + (M = Li and Na) and (H 3 BNH 2 -) 2 Ca 2+ have recently been established from the analyses of their high resolution powder diffraction data, 59,61 and that of (H 3 BNH 2 -) 2 Ca 2+ #2THF by a single-crystal X-ray determination. 60 The crystallographic determination of the [Et 3 BNH 2 BH 3 ] -K + #18-crown-6 complex in Figure 4.17, 29 confirmed that following AB nitrogen-deprotonation by the triethylborohydride, the Lewis-acidic triethylborane group coordinated at the nitrogen.…”
Section: Why Does Proton Sponge Induce H 2 -Release From Ab?mentioning
confidence: 77%
“…We found 29 that AB deprotonation could also be easily achieved by its reaction with either lithium or potassium triethylborohydride (Equation 4.7), but that in these cases, a Et 3 B-stabilized anion was formed, with the observed resonances in the 11 B NMR spectra of the Li + (-7.5 (s) and -23.8 (q) ppm) and K + (-7.8 (s) and -23.6 (q) ppm) compounds being assigned based on the DFT/GIAO calculations to the BEt 3 -(calc -10.6) and terminal -BH 3 The structures of H 3 BNH 2 -M + (M = Li and Na) and (H 3 BNH 2 -) 2 Ca 2+ have recently been established from the analyses of their high resolution powder diffraction data, 59,61 and that of (H 3 BNH 2 -) 2 Ca 2+ #2THF by a single-crystal X-ray determination. 60 The crystallographic determination of the [Et 3 BNH 2 BH 3 ] -K + #18-crown-6 complex in Figure 4.17, 29 confirmed that following AB nitrogen-deprotonation by the triethylborohydride, the Lewis-acidic triethylborane group coordinated at the nitrogen. Electronic structure calculations on [H 2 NBH 3 ] -M + have predicted 59,61 that the B-H hydrogens in these complexes will be much more negatively charged and, as a result, have a higher bascity than in AB.…”
Section: Why Does Proton Sponge Induce H 2 -Release From Ab?mentioning
confidence: 77%
See 1 more Smart Citation
“…Numerous examples of catalytically amended AB were demonstrated over the course of the CHSCoE. Homogenous catalysis efforts included Lewis acids [83], non-nucleophilic bases (i.e., Proton Sponge) [84], and various transition metals [83,[85][86][87][88]. One of the most effective homogenous catalysts was demonstrated by Baker et al [89] using nickel N-heterocyclic carbene (Ni-NHC) complex generated through an in situ reaction with bis(cyclooctadiene)Ni(0).…”
Section: Ammonia Boranementioning
confidence: 99%